Is Market Orientation possible within the NHS: Whose common sense will prevail? - Tomlinson, Adam (2007)
This dissertation examines the relationship between marketing and the NHS and it members. Marketing had a previously unsuccessful introduction into the NHS and is now with the patient choice strategy ten years later being reintroduced. The NHS is a complexed public organisation with many stakeholders from specific professions all trying to influence the direction of the organisation and its behaviour. This dissertation takes a somewhat different approach to understand marketing in a public organisation by utilizing theory and methodologies from the organisational theory paradigm. The theory used is from organisational theory has considerable overlap with understanding a market orientation. Using a different approach has promoted the use of a different methodology (for original inspiration see Jacques, 1996) which is suitable to consider the social relations and is formulated from a social constructivist philosophy. The methodology, critical discourse analysis has been used to understand the social arena and the disciplinary power which control the existence of acceptable knowledge within the NHS. This has been utilised due to it application to the relationships between the subgroups and their transformation. The contribution made by the study examines the wider social context of groups involved in marketing's introduction and how they influence the process. The findings highlight several critical issues. The government and management using marketing as a tool to further their own personal interests and enforce their knowledge. The resistance from other professional groups and how marketing goes against their principles and commonsense. The piece further goes to explain how there has been change in the social acceptance of marketing and the strategy being used to introduce it. Finally the discussion of potential transformation is a possibility as marketing as a toolbox may penetrate the NHS and the changes it will bring. The study concludes with implications of the findings and the limitations which have surfaced.